2021
DOI: 10.1186/s12864-021-07418-3
|View full text |Cite
|
Sign up to set email alerts
|

One-step generation of a targeted knock-in calf using the CRISPR-Cas9 system in bovine zygotes

Abstract: Background The homologous recombination (HR) pathway is largely inactive in early embryos prior to the first cell division, making it difficult to achieve targeted gene knock-ins. The homology-mediated end joining (HMEJ)-based strategy has been shown to increase knock-in efficiency relative to HR, non-homologous end joining (NHEJ), and microhomology-mediated end joining (MMEJ) strategies in non-dividing cells. Results By introducing gRNA/Cas9 ribon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 40 publications
(54 reference statements)
0
2
0
1
Order By: Relevance
“…However, this approach has its own shortcomings. It lacks full control over the time and extent of editing and can generate complex mosaic genotypes [ 36 , 37 ], which to a certain extent can be addressed by screening embryos prior to transfer [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this approach has its own shortcomings. It lacks full control over the time and extent of editing and can generate complex mosaic genotypes [ 36 , 37 ], which to a certain extent can be addressed by screening embryos prior to transfer [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recent increase in CRISPR/Cas9 use has led to the production of specific gene-targeted cattle [ 62 64 ]. Even in cattle, germline transmission of the specific gene mutation was proven.…”
Section: Genomic Selectionmentioning
confidence: 99%
“…From these gene editing results in cattle, it has been demonstrated that the MSTN mutation is transmitted to the next generation through the germline, laying the foundation for the mass production of MSTN mutation cattle ( 52 ). On the other hand, for only males to be born, an in vitro fertilized bovine embryo, in which the SRY gene was inserted into chromosome 17 using CRISPR/Cas9, was produced, and a report was published in 2021 that a calf was successfully born ( 56 ).…”
Section: Application Of Genome-engineered Livestock ( Fig 3...mentioning
confidence: 99%